Influence Leadership And Culture Organization To Performance Village Apparatus With Motivation Work As Variables Mediation in the Subdistrict Makarti Jaya - Nasution, Rahmadhani; Idris, Muhammad; Yamaly, Fadhil (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2025)
This study aims to determine 1) the influence of leadership on the work motivation of village apparatus in Makarti Jaya Subdistrict. 2) The influence of organizational culture on the work motivation of village apparatus in Makarti Jaya Subdistrict. 3) The influence of leadership on the performance of the village apparatus in Makarti Jaya Subdistrict. 4) The influence of organizational culture on the performance of the village apparatus in Makarti Jaya Subdistrict. 5) The influence of motivation on the performance of village apparatus in Makarti Jaya Subdistrict. This type of research is Associative. The variables used by researchers are leadership variables, organizational culture, motivation, and performance. The sample in this study was the village apparatus of Makarti Jaya District, totaling 110 people selected by Cluster Random Sampling. The data used in this study were primary data with a questionnaire data collection method. The data analysis technique used was Structural Modeling Equations (SEM) with the LISREL Program Application. The results of this study indicate that (1) Leadership has a positive and significant effect on work motivation (2) Organizational culture has a positive and significant effect on work motivation (3) Leadership has a positive but not significant effect on performance (4) Organizational culture has a positive and significant effect on performance (5) Motivation has a positive and significant effect on performance (6) Work motivation does not strengthen the influence of leadership on performance (7) Work motivation does not strengthen the influence of organizational culture on performance